Effect of Operating Parameters on Photocatalytic Treatment of Synthetic Wastewater Using CaTiO3 - Mishra, Shilpa; Dom, Rekha; Sundaram, Baranidharan (Applied Environmental Research, 2024)
Photocatalysis is thought to be a long-term, environmentally friendly, economically feasible, and promising technique for treating wastewater. The development of semiconductor nanoparticles has generated a great deal of interest in the treatment of wastewater. To break down complex contaminants found in wastewater into simpler compounds, including H2O and CO2, several UV/visible light excitable nanomaterials have been explored as photocatalysts. Their effectiveness can be managed by adjusting several reaction-related parameters like the intensity of light, irradiance time, pH, catalyst dose, temperature, doping, etc. The performance of the photocatalyst in the photodegradation of contaminants is greatly affected by these parameters. The main goal of this study is to find the best operational parameters and their impact on the photocatalytic treatment of synthetic waste-water using calcium titanate (CaTiO3) nanoparticles. For this purpose, sol-gel synthesized CaTiO3 with a band gap of 3.57 eV was used. The size of the synthesized nanoparticles is smaller than 47.62 nm. The results of photocatalytic treatment of synthetic wastewater demonstrate that CaTiO3 exhibits its best photocatalytic performance at 33 W UV light, pH 6.0, and 3.33 g L-1 CaTiO3 dose with 8 hours of irradiation time. With chemical oxygen demand (COD) concentrations varying from 700 to 40000 mg L-1 at the initial stages, the percentage of COD removal under these conditions was 100% to 77%.